Phylogenetic and expression analyses of HSF gene families in wheat (Triticum aestivum L.) and characterization of TaHSFB4-2B under abiotic stress - Yun, Liu; Zhang, Yan; Li, Shi; Yang, Jingyu; Wang, Changyu; Zheng, Lanjie; Ji, Li; Yang, Jiaheng; Song, Linhu; Shi, Yong; Zheng, Xu; Zhang, Zhiyong; et al. (Frontiers in Plant Science, 2023)
The heat shock transcription factors (HSFs) family is widely present in eukaryotes including plants. Recent studies have indicated that HSF is a multifunctional group of genes involved in plant growth and development, as well as response to abiotic stresses. Here we combined the bioinformatic, molecular biology way to dissect the function of Hsf, specifically HsfB4 in wheat under abiotic stresses. In this study, we identified 78 TaHSF genes in wheat (Triticum aestivum) and analyzed their phylogenetic relationship and expression regulation motifs. Next, the expression profiles of TaHSFs and AtHSFs were analyzed in different tissues as well as in response to abiotic stress. Furthermore, to explore the role of HSFB4 in abiotic stress response, we cloned TaHSFB4-2B from the wheat variety, Chinese Spring. Subcellular localization analysis showed that TaHSFB4-2B was localized in the nucleus. In addition, We observed TaHSFB4-2B was highly expressed in the root and stem, its transcription was induced under long-term heat shock, cold, and salinity stress. Additionally, overexpression of TaHSFB4-2B suppressed seed germination and growth in Arabidopsis with salinity and mannitol treatment. It also modulated the expression of stress-responsive genes, including AtHSP17.8, AtHSP17.6A, AtHSP17.6C, CAT2, and SOS1, under both normal and stress conditions. From these finding, we propose that TaHSFB4-2B act as a negative regulator of abiotic stress response in the plant.